Update on pharmacological management of procedural sedation for children. Issue 1 (March 2016) - Roback, Mark G.; Carlson, Douglas W.; Babl, Franz E.; Kennedy, Robert M.
Abstract : Purpose of review: The review provides an update on pharmacological techniques for procedural sedation for children outside the operating room. Recent findings: An increasing number of studies of propofol, ketamine, nitrous oxide, dexmedetomidine, and intranasal administration of drugs for procedural sedation of children continue to be reported. Summary: Propofol and ketamine are commonly used for procedural sedation in children and the use of dexmedetomidine and nitrous oxide is increasing. Although the intravenous route remains the mainstay; intranasal drug administration is increasingly used for anxiolysis and moderate sedation.